DIGITAL DA’WAH AND SOCIAL CHANGE: AN ANALYTICAL STUDY OF THE TRANSFORMATION OF AUDIENCE RELIGIOUS VALUES THROUGH DA’WAH CONTENT ON YOUTUBE - Ramadhani, Suci; Abdullah; bt. Salihan, Syafawati (Fakultas Ushuluddin Adab dan Dakwah IAIN Metro-Lampung, 2025)
This study aims to analyze the transformation of religious values among audiences through digital da’wah content on YouTube. Digital da’wah emerges as a response to the development of communication technology, enabling religious messages to reach a wider audience, particularly younger generations who are highly active on social media. The research method used is descriptive qualitative with a content analysis approach. Primary data were obtained from da’wah content on several YouTube channels such as Ustadz Abdul Somad’s lectures, the Escape podcast hosted by Ustadz Felix Siauw, and the Log In podcast by Habib Ja’far. Secondary data in the form of academic journal literature were also used to strengthen the analysis. The findings indicate that da’wah content on YouTube not only enhances the spiritual aspect and audiences’ understanding of Islam, but also shapes new religious values that are more applicable in everyday life. For instance, Ustadz Abdul Somad’s lectures strengthen religious literacy and emotional closeness between audiences and the preacher. The Escape podcast contributes to a religious transformation from ritualistic practices toward more sincere and reflective worship. Meanwhile, the Log In podcast emphasizes the social dimension of digital da’wah by fostering tolerance, solidarity, and inclusivity among religious communities. Thus, this study affirms that YouTube as a medium of digital da’wah plays an important role in shaping changes in religious values while simultaneously encouraging social change in the digital era.